2001
DOI: 10.1086/321490
|View full text |Cite
|
Sign up to set email alerts
|

Dusty Debris around Solar‐Type Stars: Temporal Disk Evolution

Abstract: Using ISO-ISOPHOT, we carried out a survey of almost 150 stars to search for evidence of emission from dust orbiting young main-sequence stars, both in clusters and isolated systems. Over half of the detections are new examples of dusty stellar systems and demonstrate that such dust can be detected around numerous stars older than a few times 106 yr. Fluxes at 60 and either 90 or 100 km for the new excess sources together with improved Ñuxes for a number of IRAS-identiÐed sources are presented. Analysis of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
216
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(238 citation statements)
references
References 53 publications
17
216
5
Order By: Relevance
“…The mean fractional dust luminosity,f dust = 1.1 × 10 −3 measured for debris disk in the BPMG, agrees with the expected stage of collisional dust evolution for such ∼12 Myr systems predicted from previous observations (e.g. Su et al 2006;Liu et al 2004;Spangler et al 2001) and models (Kenyon & Bromley 2008;Wyatt et al 2007). The large scatter in f dust among co-eval stars could be a sign of stochastic collisional dust production or a consequence of BMPG's evolutionary stage, perhaps just at the onset of collisional dust cascades at t ≈ 10 Myr.…”
Section: Discussionsupporting
confidence: 88%
“…The mean fractional dust luminosity,f dust = 1.1 × 10 −3 measured for debris disk in the BPMG, agrees with the expected stage of collisional dust evolution for such ∼12 Myr systems predicted from previous observations (e.g. Su et al 2006;Liu et al 2004;Spangler et al 2001) and models (Kenyon & Bromley 2008;Wyatt et al 2007). The large scatter in f dust among co-eval stars could be a sign of stochastic collisional dust production or a consequence of BMPG's evolutionary stage, perhaps just at the onset of collisional dust cascades at t ≈ 10 Myr.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the large age uncertainties (represented by horizontal error bars) we refrain from making a fit, and instead only display dashed lines showing the expected decline for three different values of α. We conclude that the temporal evolution of the fractional dust luminosity determined from our observations is in agreement with Nilsson et al (2009), and f dust could perhaps decline as fast as the t −2 found by Spangler et al (2001), although α < 0.8 can not be excluded due to large error bars and small stellar sample. This trend will be better constrained after the completion of the ongoing APEX/LABOCA Large Programme.…”
Section: Temporal Evolution Of Debris Diskssupporting
confidence: 82%
“…Observational evidence for the presence of disks in clusters of varying ages suggests that (Spangler et al 2001). Only 30% of the members of the NIR cluster are detected in all three bands, and half of those appear to have circumstellar material.…”
Section: Circumstellar Materials Around Members Of the Nir Clustermentioning
confidence: 93%